2018
DOI: 10.3389/fnhum.2018.00326
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Psychological Perspectives of Resilience: Is It Possible to Improve Stress Resistance?

Abstract: The term “resilience” refers to the ability to adapt successfully to stress, trauma and adversity, enabling individuals to avoid stress-induced mental disorders such as depression, posttraumatic stress disorder (PTSD) and anxiety. Here, we review evidence from both animal models and humans that is increasingly revealing the neurophysiological and neuropsychological mechanisms that underlie stress susceptibility, as well as active mechanisms underlying the resilience phenotype. Ultimately, this growing understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 153 publications
2
74
0
1
Order By: Relevance
“…For example, as mentioned previously, it has been suggested that under chronic stressors, perceived uncontrollability results in diminished HPA activity and that this decrease may lie behind the withdrawal behaviors that correspond to cynicism (Heim et al, 2000). As self-efficacy moderates the influence of job stressors on perceived controllability (Liu et al, 2018), one might argue that employees with a low sense of selfefficacy facing high job demands are more likely to perceive these demands as uncontrollable, resulting in lowering of the cortisol secretion required to cope with demands and distancing from work as a defensive strategy, transitioning into the cynicism phase. In contrast, employees exposed to high job demands but with a high sense of self-efficacy are more likely to perceive these as manageable, increasing mobilization of energetic resources -high HPA activity -to actively cope with demands, resulting in more exhaustion due to increased effort, but not in withdrawal.…”
Section: Limitations and Future Researchmentioning
confidence: 90%
“…For example, as mentioned previously, it has been suggested that under chronic stressors, perceived uncontrollability results in diminished HPA activity and that this decrease may lie behind the withdrawal behaviors that correspond to cynicism (Heim et al, 2000). As self-efficacy moderates the influence of job stressors on perceived controllability (Liu et al, 2018), one might argue that employees with a low sense of selfefficacy facing high job demands are more likely to perceive these demands as uncontrollable, resulting in lowering of the cortisol secretion required to cope with demands and distancing from work as a defensive strategy, transitioning into the cynicism phase. In contrast, employees exposed to high job demands but with a high sense of self-efficacy are more likely to perceive these as manageable, increasing mobilization of energetic resources -high HPA activity -to actively cope with demands, resulting in more exhaustion due to increased effort, but not in withdrawal.…”
Section: Limitations and Future Researchmentioning
confidence: 90%
“…Resilience is a relatively new construct that may be an important factor ( 26 ). Resilience is the ability to successfully adapt to stress, trauma, or adversity, enabling individuals to avoid stress-induced mental disorders, such as depression, posttraumatic stress disorder, and anxiety ( 27 , 28 ). In this regard, exploring how to build resilience may be useful in assisting children affected by anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…According to our model, cognitive appraisal and emotional experience influence the coping strategies employed for symptom adjustment. Therefore, cultural differences are also evident in the individual choice of coping strategies [65].…”
Section: Discussionmentioning
confidence: 99%